Interfaz gráfica en Matlab para determinar los índices de vegetación y agua de diferencia normalizada en imágenes multiespectrales del satélite PerúSAT-1. - Huamaní Navarrete, Pedro Freddy (2024)
This research aimed to calculate and visualize the Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Water Index (NDWI) by processing freely available multispectral satellite images from the PeruSAT-1 satellite. The images covered the coastal area and three districts in southern Lima, Peru. The methodology applied image processing using MATLAB’s App Designer interface under segmentation and multispectral analysis techniques to extract relevant data from the available RGB and NIR spectral bands. Image correction and enhancement, meticulously performed, were also carried out to ensure the extracted data were accurate and useful for subsequent analyses. Additionally, the developed application enabled the visualization of the NDVI and NDWI indixes. It provided representations of the histograms of the four spectral bands and the profile and average reflectance.